Grafting of Tomato with Eggplant Rootstock at Penyabangan Village Payangan Subdistrict of Gianyar Bali - Kariada, I. Ketut; Aribawa, I. B. (KnE Life Sciences, 2017)
Grafting on tomatoes is performed to obtain tomato plants that are resistant to bacterial wilt, waterlogging resistant, resistant to fusarium wilt and nematodes. Bacterial wilt caused by Ralstonia solanacearum causes the tomatoes grown in the rainy season to wilt and die. These bacteria live in the soil and invade plants through roots. To overcome this disease, grafting was carried out by using resistant eggplant as rootstock. This method is expected to reduce the attack of bacterial wilt diseases on tomato plants. The study was conducted in the village of Penyabangan Payangan Gianyar in FY 2014. This area was located at the plateau of AEZ wet climate. The experimental design used was a randomized block design (RBD) with two treatments and 10 replications. Materials used were tomato plants that have been joined with eggplant rootstock (grafted) and tomato plants without root stock (non-grafted) for comparison. The varieties used were varieties F1 Marta. In field applications, the scion was prevented from touching the ground while the rootstock was fully embedded into the ground. Based on the plant height, there was a slower growth of the grafted tomato plants compared with that of non-grafted one in the early stages of growth but became normal in generative phase. It was also found that the yield of the grafted tomato was lower (2.54 kg. tree-1) than that of the non-grafted one (3.19 kg.tree-1). Keywords: grafting; tomatoes; eggplant; stem rot; bacterial wilt (alphabetic in order).